LA COMUNIDAD DE LA UTOPÍA Y DE LA MUERTE. APUNTES SOBRE PENSAR ENTRE ÉPOCAS DE NICOLÁS CASULLO (Hologramática, 2023)
From his disenchantment with history, Nicolás Casullo thought of the utopian as a nightmarish substrate of politics due to its ability to reinvent the world, simply by narrating it differently.And he writes about utopian generations with one condition: that this political history be told from a cultural reflection that currently recodes and largely replaces the comprehensive worlds.He will consider a political, generational project utopian, if with such a denomination he supplants his references, his definitions, his truths and behaviors, by a reading that is constituted (at the time he writes) in the context of cultural studies on the so-called tradition modern and no longer from the lexicon of the idea of revolution itself.That is to say, in the present as a reading of the revolution as the past. This formula appears defined in Pensar entre épocas, where he insists on a reading from the antipodes of the courses, where the revolution never dreamed of thinking.In this same work, Casullo thought of an idea of community that would also be his infinite absence, “what does not end up being constituted in his name, or what collapses in his name.What is finally constituted to show its inability to be so, which always requires an essay of the world to think about it and pursue it ”(2004b: 80). This is an unusual reflective experience, of feeling inhabiting the expiration of the community not proposed as a way of ignoring ordenying that memory tends to the opposite of death, that is, to transmit the ceremony that makes it and shapes it, to recompose what has been left unarmed.This essay aims to investigate in an essayistic way the relationship between both concepts (utopia and death) around the idea of community that we can appreciate in Casullo's work.
Keywords: Casullo; Community; Utopia; Death; Myth